Receptor for advanced glycation end products (RAGE) knockout reduces fetal dysmorphogenesis in murine diabetic pregnancy - Ejdesjö, Andreas; Brings, Sebastian; Fleming, Thomas; Nawroth, Peter Paul (Reproductive toxicology, 2016)
The receptor for Advanced Glycation End products (RAGE) is implicated in the pathogenesis of diabetic complications, but its importance in diabetic embryopathy is unclear. We therefore investigated the role of RAGE in diabetic embryopathy using streptozotocin induced diabetes in female wild type (WT) C57Bl/6N and RAGE knockout C57Bl/6N (RAGE−/−) mice, mated with control males of the same genotype. Maternal diabetes induced more fetal resorption and malformation (facial skeleton, neural tube) in the WT than in the RAGE−/− fetuses. Maternal plasma glucose and methylgyoxal concentrations, as well as embryonic N(ε)-carboxymethyl-lysine (CML) levels were increased to the same extent in diabetic WT and RAGE−/− pregnancy. However, maternal diabetes induced increased fetal hepatic isoprostane 8-iso-PGF2α levels (oxidative stress marker) and embryonic activation of NFκB in WT only (not in RAGE−/− embryos). The association between RAGE knockout and diminished embryonic dysmorphogenesis in diabetic pregnancy suggests that embryonic RAGE activation is involved in diabetic embryopathy.